Isolamento e caracterização de amido de chuchu - Cruz, Renato; A El Dash, Ahmed (Revista Ceres, 2025)
The objectives of the present work were to isolate and characterize the chayotte starch. The choice of the chayotte as a starch source, in spite of its low starch conten (2.8%), was based on the fact that this a plant has a wide distribution in Brazil with a high yield per unit area (more than 150 tons/ha/year) by simple cultural practices and harvesting mechanisms. The starch content on a dry matter basis was 37% of whick only 46.4% was extracted.